2010
DOI: 10.1021/ja106925f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Water-Tolerant Indium Homoenolate in Aqueous Media and Its Application in the Synthesis of 1,4-Dicarbonyl Compounds via Palladium-Catalyzed Coupling with Acid Chloride

Abstract: The first water-tolerant, ketone-type indium homoenolate was synthesized via the oxidative addition of In/InCl(3) to enones. The reaction proceeds exclusively in aqueous media. Both indium and indium(III) chloride are necessary for the smooth conversion of the reaction. Similar results were obtained when InCl or InCl(2) was used in place of In/InCl(3). The synthetic utility of the indium homoenolate was demonstrated through the synthesis of 1,4-dicarbonyl compounds via palladium-catalyzed coupling of indium ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(30 citation statements)
references
References 90 publications
0
30
0
Order By: Relevance
“…Indium can also be used to generate isolable carbon‐bound homoenolates. In 2010, Loh showed that treatment of vinyl ketones 67 with indium metal in the presence of indium(III) chloride gives the corresponding indium homoenolate 68 (Scheme ) . Not only are these indium homoenolates water‐stable, but they were shown to be viable in palladium‐catalyzed cross‐coupling with acyl chlorides and, in a later report, with aryl halides, making indium reagents 68 easy‐to‐access and synthetically useful homoenolates.…”
Section: Synthesis Of Homoenolatesmentioning
confidence: 99%
“…Indium can also be used to generate isolable carbon‐bound homoenolates. In 2010, Loh showed that treatment of vinyl ketones 67 with indium metal in the presence of indium(III) chloride gives the corresponding indium homoenolate 68 (Scheme ) . Not only are these indium homoenolates water‐stable, but they were shown to be viable in palladium‐catalyzed cross‐coupling with acyl chlorides and, in a later report, with aryl halides, making indium reagents 68 easy‐to‐access and synthetically useful homoenolates.…”
Section: Synthesis Of Homoenolatesmentioning
confidence: 99%
“…Azedolysis of α,β‐epoxy carboxylic acid with NaN 3 , [24] Polymerization, [25] cyclisation, [26] ring opening reaction of chalcone epoxides with indole and pyrrole [27] are the most important reactions in organic synthesis promoted by InCl 3 . On the basis of environmental consideration, InCl 3 alone and In/InCl 3 system applied in aqueous media for the synthesis of fused pyrimidines and pyrazoles [28] and indium homoenolate (organoindium complex) [29] respectively. Moreover, InCl 3 can be recycled after the synthesis of isatin N ‐ribonucleosides [30] from N ‐phenylribosylamines and diethyl oxalate under microwave irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, numerous multistep approaches to unsymmetrical 1,4-dicarbonyl compounds involving, e.g., S N 2-type displacements [ 1 ] or highly functionalized substrates such as β-ketoesters [ 2 3 ] or β-ketosulfones [ 4 ] have been developed. Recently, Loh reported the palladium-catalyzed coupling of an acid chloride with premade isolable indium homoenolates (In(CH 2 CHRC=OR') 2 ), 1.2 equiv relative to the acid chloride) to give the corresponding 1,4-diketones [ 5 ]. Yet the direct coupling of two enolates is inarguably the shortest and most direct path to 1,4-dicarbonyl compounds.…”
Section: Introductionmentioning
confidence: 99%